(untitled) (Al-Academy, 2015)
The art of calligraphy is regarded as one of the tremendous and distinct products in the history of Islamic arts through the unparalleled high ranks it reached to, until it gained Islam’s indication and became a symbol for it, in terms of its function linked to the calligraphy of the holy Qur’anic texts, where this merit formed a strong impulse in seeking its development, the emergence of the calligraphic constructs, including the calligraphic straps, is one of this continual seeking products, and an advanced stage at the level of technical and expressive development, and also one of the natural results generated by the development of fonts and the increase of their employing methods through what they recorded at the level of formal characteristics and their structural levels systems. Yet, the absence of the critical analytical aspect of these works resulted in the weakness of their aesthetic visions, since these products were not confined on only mere calligraphic accommodations, but they reflected the establishment of calligraphic and decorative varieties in terms of various revealing techniques; therefore, these products were not empty of artistic and designing problematic especially which became unfitted with the superiority of this sublime art. Because this topic was not studied in a way that transforms its problematic and explains its dimensions, and employment concepts, which all were focused within the topic (the diversity of the extraction methods of calligraphic straps at Baghdad’s mosques)